Critical appraisal of the role of serum albumin in cardiovascular disease - Shih-Chieh Chien; Chun-Yen Chen; Chao-Feng Lin; Hung-I Yeh (BMC, 2017)
Abstract Concentration of serum albumin (SA), a multifunctional circulatory protein, is influenced by several factors, including its synthesis rate, catabolism rate, extravascular distribution, and exogenous loss. Moreover, both nutritional status and systemic inflammation affect the synthesis of SA. Determining SA concentration aids in risk prediction in various clinical settings. It is of interest to understand the prognostic value of SA in the full spectrum of cardiovascular disease (CVD) in the era of newly developed pharmacological and interventional treatments. Proper interpretation of SA in addition to established risk factors potentially provides a better risk discrimination and thereby presents an option to modify therapeutic strategies accordingly. In this narrative review, we summarize the basic features of SA and its associated physiological functions contributing to its prognostic impacts on CVD. Finally, we discuss the prognostic role of SA in CVDs based on existing evidence.